Transmission of Bacterial Infections by Dental Impression (Texas Journal of Medical Science, 2022)
The aim of this research is to evaluate the type of transmission of bacterial infections by dental impression. Samples were collected from the clinics of the Dentistry College-University of Dhi-Qar. After obtaining the consent of both the patient and the doctor taking two swabs from the same patient, the first swab from the patient’s mouth and the second from the Alginate impression. Each sample specimen's was inoculated onto appropriate plates, such as blood agar and MacConkey agar for standard aerobic development, and used the biochemical characterization and identification of these isolates at genus and species levels was confirmed using the analytical profile index (API) assays, and then the automated device VITEK 2. The result appear different signification between all the groups that divided to it that return to Dental patients are high-risk patients relative to their potential to transmit as well as acquire an infectious disease